HUBUNGAN KEBUTUHAN AFILIASI DENGAN INTENSITAS PENGGUNAAN JEJARING SOSIAL TWITTER PADA REMAJA AKHIR - I Putu Galang Dharma Putra; Adijanti Marheni (Jurnal Psikologi Udayana, 2015)
McClelland said that one of three major human needs is the need for affiliation, or the need to establish relationships with other people who are generally at its peak when someone is at the stage of adolescence. One way to establish a relationship with another individuals is by communicate. One medium that people uses to communicate is internet. Twitter is one of many internet-based social media that often used by the adolescence. Various things communicated by teenagers on Twitter, from positive tweets, or even the controversial one. Thus, makes their intensity of adolescence’s tweets, because adolescence wants to established a communication with other people in order to satisfy their need for affiliation. Therefore, it can be assumed that adolescence’s need for affiliation is related to their intensity of Twitter usage A total of 415 adolescence aged between 18-21 years old were becoming subjects of this research. This study uses quantitative method with correlational approach. The sampling technique was multistage cluster sampling. The instruments that used in this research are the need for affiliation scale (21 items), and the intensity of twitter usage scale (2 items), with the need for affiliation scale’s reliability coefficient of 0.815 The main data in this research were processed by using the nonparametric Spearman correlation analysis with a correlation value of 0.342 and a probability value of 0.000. The supporting data were also processed using the nonparametric analysis to see the difference between subjects’ demographic data. The results indicate that the needs for affiliation variable and intensity of Twitter usage variable did not differ significantly by gender of respondents, however, it differ significantly based on age and length of ownership of the subjects’ Twitter account. Keywords: Need for affiliation, intensity, Twitter, adolescence.